2019
DOI: 10.1097/iop.0000000000001124
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Expansion in Cranial Vault After Minimally Invasive Extradural Transorbital Decompression for Thyroid Orbitopathy

Abstract: With wide exposure of the middle cranial fossa dura following extradural transorbital decompression, orbital tissue typically expands in the cranial vault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Such a large reduction in proptosis is not always necessary (our mean proptosis was 24.51 ± 1.76 mm preoperatively). In cases needing significant reduction of proptosis, a medial decompression can be associated, widely exposing the dura [54]. We did not encounter any CSF leak.…”
Section: Discussionmentioning
confidence: 90%
“…Such a large reduction in proptosis is not always necessary (our mean proptosis was 24.51 ± 1.76 mm preoperatively). In cases needing significant reduction of proptosis, a medial decompression can be associated, widely exposing the dura [54]. We did not encounter any CSF leak.…”
Section: Discussionmentioning
confidence: 90%
“…Another notable feature of this report was the possibility for greater exposure of the dura. Although the report merely explained that the dura mater becomes a posterior anatomical landmark, another report published by Goldberg et al presented evidence of more effective decompression [26]. Goldberg et al [20] showed that exposing the dura, which is in contact with the posterior…”
Section: Journal Of Endocrinology and Thyroid Researchmentioning
confidence: 99%
“…3). 27 The deep lateral wall is approached through a lateral eyelid crease incision, with wide periosteal dissection from the mid-superior orbital rim to the mid-inferior orbital rim and back to the superior and inferior orbital fissures (Fig. 3).…”
Section: Systematic Approachmentioning
confidence: 99%